2012
DOI: 10.1001/jama.2012.6434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screening for Partner Violence on Women's Quality of Life

Abstract: Context-Although partner violence screening has been endorsed by many health organizations, there is insufficient evidence that it has beneficial health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 20 publications
1
89
0
3
Order By: Relevance
“…35,36 This research suggests that routine screening for IPV in the absence of a routine intervention is not effective in reducing IPV mortality and morbidity, 34 A recent systematic review of 16 ''brief'' (described as 3 or fewer hours of contact) IPV interventions delivered in health care settings identified several common components: safety planning, increasing motivation, and setting goals to reduce IPV and improve safety, linking women to IPV-related services and increasing social support. 37 Because of significant methodological limitations, only six were included in the effectiveness review.…”
Section: Conducting Assessment Brief Intervention and Improved Linkmentioning
confidence: 99%
“…35,36 This research suggests that routine screening for IPV in the absence of a routine intervention is not effective in reducing IPV mortality and morbidity, 34 A recent systematic review of 16 ''brief'' (described as 3 or fewer hours of contact) IPV interventions delivered in health care settings identified several common components: safety planning, increasing motivation, and setting goals to reduce IPV and improve safety, linking women to IPV-related services and increasing social support. 37 Because of significant methodological limitations, only six were included in the effectiveness review.…”
Section: Conducting Assessment Brief Intervention and Improved Linkmentioning
confidence: 99%
“…[3] However, more recently a rigorously conducted randomised controlled trial (the WEAVE study) found no difference in primary outcomes between women who were routinely screened for violence and a control group. [4] This trial, in addition to prior evidence, [5,6] has led to the expert conclusion that universal screening for IPV is ineffective in improving health. [7] Although screening is able to identify women experiencing IPV, uptake of interventions is impeded by numerous barriers and is often low, and current intervention approaches have not yet proved beneficial in asymptomatic women.…”
Section: Intimate Partner Violence: How Should Health Systems Respond?mentioning
confidence: 99%
“…43,44 Understanding the integration of screening with the support services that follow emerged as a central research gap. Short of the KP model, whose systems approach enables tracking patients after intervention and referral, little research exists on what happens for women after a positive screen, yet tracking this process is central to understanding the impact of screening, as many harm-reduction and safety enhancement steps occur outside of the clinical setting.…”
Section: Lessons Learnedmentioning
confidence: 99%